Silyl‐Substituted Planar Chiral Phosphoric Acids with Ferrocene‐bridged Paracyclophane Frameworks: Synthesis, Characterization, and Uses in Enantioselective aza‐Friedel‐Crafts Reactions. Issue 3 (19th December 2016) - Stemper, Jérémy; Isaac, Kévin; Ghosh, Nayan; Lauwick, Hortense; Le Duc, Gaëtan; Retailleau, Pascal; Voituriez, Arnaud; Betzer, Jean‐François; Marinetti, Angela
Abstract: This manuscript reports on a suitable method for the synthesis of paracyclophane type, ferrocene‐bridged chiral phosphoric acids, which bear silyl‐substituents on their paracyclophane frameworks. These acids have been obtained easily in enantiomerically pure form, by taking advantage of ( S )‐(1‐phenyl‐2‐cyanoethyl)phosphorodiamidite as a phosphorylating agent. They have been used then as catalysts for aza‐Friedel‐Crafts reactions between indoles and imines, giving high catalytic activity and up to 98% enantiomeric excess. Abstract :